Pengaruh Saluran Aerasi pada Pengomposan Berbahan Baku Jerami - I Wayan Budiarta; Sumiyati Sumiyati; Yohanes Setiyo (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2017)
Crop residues such as supreme variety rice straw can reach about 25 ton/ha which can be used as raw material for composting. The purpose of this research were to determine the effect of channels aeration of the composting process, and to find the compost quality produced from rice straw. Two treatments were conducted, namely: P1 : rice straw composting with aeration channel; P2 : rice straw composting without aeration channel. About 1.5 m long, 1 m wide and 1 m high of dimension of compost heap respectively were conducted. The parameters measured were temperature, humidity, water content, yield, pH, nitrogen, carbon and C/N ratio. The composting process lasted for 12 weeks. The composting process in the composting treatment with aeration channels tend to run slower than composting treatment without aeration channels. The quality of the compost produced from rice straw on the treatment P1 and P2 were appropriate the standard compost appointed by Peraturan Menteri Pertanian Nomor 70/Permentan/SR.140/10/2011.